Fiscal Policies for Paris Climate Strategies-from Principle to Practice. (Policy Papers; Policy Paper, 2019)
This paper discusses the role of, and provides practical country-level guidance on, fiscal policies for implementing climate strategies using a unique and transparent tool laying out trade-offs among policy options.